(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Chickenpox is one of the most widespread highly contagious infections, the susceptibility to which reaches 95-100%. Against the background of a decrease in the incidence of “preventable” infections in the structure of infectious pathology, the importance of chickenpox increases. Infection with the Varicella Zoster virus (VZV), usually in adults, leads to lifelong latent persistence of the pathogen in the body of a person who has had chickenpox with a high probability, often after many years, of its endogenous reactivation and the development of such a severe, debilitating disease as herpes zoster (shingles). [4,5]